WAYS OF SUPPORT AND DEVELOPMENT OF SOCIAL ACTIVITY IN THE EL- DERLY - Піонтківська, Олена Георгіївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article highlights the main directions of elderly people social activity research. Also the article contains an analysis of approaches to the defiition of social activity, and its difference from public activity. The article presents the model of social activity of elderly people. This model of social activity consists of4 levels: individual social activity, public activity, community activity and civic activity. All these levels are characterized by different positions of elderly people and the degree of their involvement in these activities.Also, the article contains the results of empirical study on the socio-psychological characteristics of elderly people, which inflence the participation in social activity and indicators that affect the increase and decrease of elderly people social activity. Authors found that participation in social activity is inflenced bythe following socio-psychological characteristics: self-esteem level of personality, level of social support, personal social orientation, interests and needs of the elderly, components of the structure of person value orientations. The important place is occupy by the specifis of the implementation of social and psychological support as readiness of specialists to work with this category to use the latest technologies of social work;support of the close environment of the elderly in internal potential revealing; development of the externalsubjectivity of the active life position of the elderly.The article contains a model of socio-psychological support of elderly people social activity, which includes three programs. The fist program includes the group of personal growth for the elderly. Work in the group of personal growth is aimed at the development of those personal qualities. The second program includes conducting mutual support and mutual assistance groups for the elderly. The third program includeswork directly with those specialists and volunteers who carry out or may carry out socio-psychological support for the elderly, and also provides training and retraining of such specialists in accordance with the new approach of work with this category. An important place in the implementation of programs for socio-psychological support of the elderly social activity is the implementation of social projects and programs developed by the most part of this category. The ways of further using the obtained results and implementation of the developed programs are outlined.